Finnish pediatric surgery hub – From centralization to collective learning and sharing of expertise - Pakarinen, Mikko P.; Luoto, Topi; Nuutinen, Susanna; Raitio, Arimatias; Tahkola, Esko; Koivusalo, Antti (Elsevier, 2025)
Aim of the study
Continuous surgical developments, growing awareness of patient representatives and limited health-care resources are pushing for innovative approaches to ensure equal high-quality pediatric surgical care. We aimed to describe early experiences and assess surgical safety of a novel nationwide pediatric surgery collaborative initiative.
Methods
In 2021, general pediatric surgeons representing all five independent university hospitals performing neonatal surgery in Finland initiated national collaboration, the Finnish pediatric surgery hub (FPSH), for sharing of surgical expertise and collective learning. For each case addressed by FPSH, place of care and surgical team were decided individually, and when deemed necessary, operations were performed in cooperation. Operations performed during 2021–2023 and associated early (<30 days) postoperative complications were analyzed according to Clavien-Madadi classification.
Results
Of the total 40 surgeries managed co-operatively by FPSH, 30 (75%) took place in local university hospitals and 10 in Helsinki University Hospital. There were 34 (85%) elective and 6 urgent cases, which were operated within median 1 (range, 1–3) days. Most frequent underlying diagnoses included anorectal malformations, esophageal atresia and Hirschsprung disease. Overall, 12 (30%) had any early postoperative complications, all Clavien-Madadi grade IIIB or lower, and five patients (13%) were reoperated. Rate or grade of complications was not associated with place of care. In addition to regular virtual case meetings, national care protocols and research projects were introduced.
Conclusion
These preliminary findings suggest that our national collaborative initiative, FPSH, not only provided practical and safe framework for sharing of surgical expertise but also for collective learning.